Адміністративно-правові форми забезпечення цивільного захисту на регіональному рівні - Остап'юк, А. Ю.; Ostapiuk, A. Yu. (Європейські перспективи. - 2024. - № 2. - С. 280-285, 2024)
Встановлено, що адміністративно-правові форми забезпечення цивільного захисту на регіональному рівні найбільш доцільно розуміти як зовнішній прояв практичної діяльності спеціально уповноважених суб’єктів, яка спрямована на створення сприятливих правових, організаційних, управлінських, економічних та інших умов для функціонування даного інституту в рамках певного регіону. До вказаних форм віднесено: нормотворчість, видання індивідуальних адміністративно-правових актів, координація, укладення адміністративних договорів, вчинення організаційних та матеріально-технічних дій. Аргументовано, що нормотворчість, як форма забезпечення цивільного захисту на регіональному рівнів, полягає у тому, що за її допомогою спеціально уповноважені суб’єкти в межах своєї компетенції можуть приймати нормативно-правові акти, положення яких формують правове поле їх діяльності та реалізації функцій та завдань. Саме через нормотворчу діяльність вбачається можливим закріпити правовий порядок та особливості реалізації завдань забезпечення цивільного захисту в межах регіону за відповідними напрямами.

It has been established that the administrative and legal forms of civil protection at the regional level are most expediently understood as an external manifestation of the practical activity of specially authorized subjects, which is aimed at creating favorable legal, organizational, managerial, economic and other conditions for the functioning of this institute within the framework of a certain region . These forms include: rule-making, issuance of individual administrative and legal acts, coordination, conclusion of administrative contracts, execution of organizational and material and technical actions. It is argued that rule-making, as a form of ensuring civil protection at the regional level, consists in the fact that with its help, specially authorized subjects within the limits of their competence can adopt normative legal acts, the provisions of which form the legal field of their activities and the implementation of functions and tasks . It is through the rule-making activity that it is considered possible to consolidate the legal order and specifics of the implementation of the tasks of providing civil protection within the region in the relevant directions. It is summarized that the administrative and legal forms of providing civil protection at the regional level, given in the article, most meaningfully and fully characterize the practical content of such activities. At the same time, a significant drawback is that most of the forms outlined in the article have not found their legislative consolidation and proper regulation, which significantly complicates law enforcement practice. That is why an important task of the legislator is to expand not only the circle, but also the content of the researched forms.

Установлено, что административно-правовые формы обеспечения гражданской защиты на региональном уровне наиболее целесообразно понимать как внешнее проявление практической деятельности специально уполномоченных субъектов, направленную на создание благоприятных правовых, организационных, управленческих, экономических и других условий для функционирования данного института в рамках определенного региона. К указанным формам отнесены: нормотворчество, издание индивидуальных административно-правовых актов, координация, заключение административных договоров, совершение организационных и материально-технических действий. Аргументировано, что нормотворчество как форма обеспечения гражданской защиты на региональном уровне заключается в том, что с ее помощью специально уполномоченные субъекты в пределах своей компетенции могут принимать нормативно-правовые акты, положения которых формируют правовое поле их деятельности и реализации функций и задач. Именно через нормотворческую деятельность представляется возможным закрепить правовой порядок и особенности реализации задач обеспечения гражданской защиты внутри региона по соответствующим направлениям.
Keywords: форма; адміністративно-правова форма; забезпечення; цивільний захист; регіональний рівень; form; administrative and legal form; provision; civil protection; regional level; административно-правовая форма; обеспечение; гражданская защита; региональный уровень